Public Digital Libraries: Observations and Prospects from the Chinese Experience. Issue 2 (15th March 2018) - Huang, Yurong
ABSTRACT: In recent years, the digital revolution has created both challenges and opportunities for cultural industries. The ever-increasing production and diffusion of culture through new media via the Internet have profoundly challenged the basic infrastructure and modes of operation in many sectors of the cultural industries. This has been most evident in the case of heritage organizations—including public libraries—where the digital revolution has brought with it a number of significant challenges with respect to courting visitors/users and remaining relevant in the context of evolving digital technologies. This article discusses the rise and evolution of public digital libraries in the 1990s as a response to these new challenges. After formulating some observations about this global trend, which is now more than two decades old, this article discusses the case of public digital libraries in China. In particular, this article points to the importance of cultural policy for the development of this new form of cultural institution. Finally, after reviewing some of the challenges faced by most of these new digital libraries, this article discusses the importance of professional culture in addressing the changing needs of users.